2020
DOI: 10.1177/1078345820939183
|View full text |Cite
|
Sign up to set email alerts
|

Fatherhood, Reproductive Health, and Incarcerated Men: A Qualitative Study With Implications for Reentry

Abstract: It is important to understand how incarcerated men conceptualize fatherhood for reentry. Sixteen interviews explored attitudes and feelings about parenthood, family planning, and challenges and strengths regarding fatherhood. Transcriptions were analyzed for themes using open coding. Parenting themes: being active in children’s lives, financial stability, and giving children better lives. Family planning themes: preventing sexually transmitted infection, creating stable families, importance of family planning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The intervention was modified from work involving boys found in high-risk settings, including incarceration (Bassett et al, 2021). It was adapted specifically for incarcerated men to address their particular family planning needs (see Laird et al, 2020). A PhD-level behavioral scientists with almost 30 years of experience tailored the intervention based on prior work in MI, the Trans-Theoretical Model (TTM), and work in incarcerated settings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention was modified from work involving boys found in high-risk settings, including incarceration (Bassett et al, 2021). It was adapted specifically for incarcerated men to address their particular family planning needs (see Laird et al, 2020). A PhD-level behavioral scientists with almost 30 years of experience tailored the intervention based on prior work in MI, the Trans-Theoretical Model (TTM), and work in incarcerated settings.…”
Section: Methodsmentioning
confidence: 99%
“…This population already deals with financial insecurity and employment difficulty which put them at risk for recidivism (Berghuis, 2018). Furthermore, in a recent qualitative study (Laird et al, 2020) with incarcerated men, many participants expressed wanting to learn more about and to receive resources on family planning, as well as wanting to achieve financial stability before having any or more children.…”
Section: Unplanned Partner Pregnancy and Stis Among Incarcerated Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on men and women justice-involved individuals suggest that a good returning father is expected to work hard to provide for the children financially (Laird et al, 2020). For example, a recent study based on a group of incarcerated fathers revealed that respondents considered financially supporting their children to be the main task in reentry (e.g., Laird et al, 2020). One respondent said that “I can’t go back to that life, I have to work 10 times as hard, so I can support her and support myself” (Laird et al, 2020, p. 271).…”
Section: The Gender-specific Meanings Of a Good Returning Parentmentioning
confidence: 99%
“…For example, a recent study based on a group of incarcerated fathers revealed that respondents considered financially supporting their children to be the main task in reentry (e.g., Laird et al, 2020). One respondent said that “I can’t go back to that life, I have to work 10 times as hard, so I can support her and support myself” (Laird et al, 2020, p. 271). Another respondent said that he would make sure to provide for his children so they would not end up in prison as he did (Laird et al, 2020, p. 271).…”
Section: The Gender-specific Meanings Of a Good Returning Parentmentioning
confidence: 99%